(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The study sought to establish the effectiveness of the various teaching methods on the acquisition of the English language skills. The study was carried out in public secondary schools in Nairobi County. The objectives sought to find out the various teaching methods used in English language, the effectiveness of the lecture methods on acquisition of English language skills; the role of role playas a teaching method in promoting acquisition of English language skills and the effectiveness of questions and answer methods on acquisitions of English language skills. Four research questions were formulated to guide the study.